1992
DOI: 10.1021/bi00147a015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and channel-forming characteristics of gramicidin K's: a family of naturally occurring acylated gramicidins

Abstract: The gramicidin K family is a set of naturally occurring acylated linear peptides in which a fatty acid is esterified to the ethanolamine hydroxyl of either gramicidin A or C, and possibly also to gramicidin B (Koeppe, R. E., II, Paczkowski, J. A., & Whaley, W. L. (1985) Biochemistry 24, 2822-2826). These acylated gramicidins form membrane-spanning channels in planar lipid bilayers and therefore constitute a model system with which to study the structural and functional consequences of acylation on membrane pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…Also labeled in Figure 2 are the long-range NOESY cross peaks that are indicative of a right-handed /363 helix, NH,-CaH,+6 for even i and NH,-CaH,-6 for odd i (Arsen 'ev et al, 1985;Koeppe et al, 1994b). This NMR evidence for the retention of backbone structure is in agreement with previous data that include the similar circular diehroism spectra of gA and acyl-gA (Vogt et al, 1991) and the hybrid channel formation between acyl-gA and right-handed /363helical reference compounds (Williams et al, 1992).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Also labeled in Figure 2 are the long-range NOESY cross peaks that are indicative of a right-handed /363 helix, NH,-CaH,+6 for even i and NH,-CaH,-6 for odd i (Arsen 'ev et al, 1985;Koeppe et al, 1994b). This NMR evidence for the retention of backbone structure is in agreement with previous data that include the similar circular diehroism spectra of gA and acyl-gA (Vogt et al, 1991) and the hybrid channel formation between acyl-gA and right-handed /363helical reference compounds (Williams et al, 1992).…”
Section: Resultssupporting
confidence: 91%
“…Functionally, the acylation of gA does not alter the singlechannel conductance for Na+ or Cs+, but it does increase the mean channel lifetime 5-fold (Koeppe et al, 1985;Vogt et al, 1992). Previous studies have demonstrated that acylation does not notably affect the structure of the gA backbone (Vogt et al, 1991(Vogt et al, , 1992Koeppe et al, 1992;Williams et al, 1992). Nothing is known about the possible influence of acylation on the orientation and dynamics of side chains.…”
mentioning
confidence: 98%
“…The convergent results also suggest that the gA channel structures in SDS and DMPC environments are highly similar. The solid-state approach, due to its high sensitivity, will also prove valuable as a difference method for examining the effects of sequence changes (e.g., Durkin et al, 1990), fatty acylation (Williams et al, 1992;Vogt et al, 1992;Koeppe et al, 1993), or other covalent modifications to the gramicidin channel. Side chain-side chain and side chain-lipid interactions are expected to be revealed through changes in the 2H NMR spectra that reflect different side chain orientations and/or dynamics.…”
Section: Comparison Of Nmr Methodsmentioning
confidence: 99%
“…It is thought that the variation in dipole moments affect long range ion-dipole interactions critical for ion conduction. In addition, variation of the amino acid residue at position 11 (e.g., Trp, Phe, or Tyr) also induces changes in the average lifetime of channel species (Mazet et al, 1984;Becker et al, 1991;Williams et al, 1992;Andersen et al, 1998). The average single-channel lifetime is a measure of the gramicidin dimer dissociation rate constant (Becker et al, 1991), and provides a measure of channel stability in a bilayer mimetic.…”
Section: Introductionmentioning
confidence: 99%